Fast pixelated sensors for radiation detection and imaging based on quantum confined structures in III/V semiconductors. (8th March 2017) - Tortora, M.; Biasiol, G.; Cautero, G.; Menk, R.H.; Plaisier, J.R.; Antonelli, M.
Abstract: In order to improve the characterisation of the delivered beams in many types of photon sources, innovative beam profilers based on III/V semiconductor materials (InGaAs/InAlAs) have been deeply investigated. Owing to a tunable and direct band gap these devices allow radiation detection in a wide spectral range. In order to increase the sensitivity of the device in radiation detection charge amplification on the sensor level is implemented. This is obtained by exploiting In 0.75 Ga 0.25 As/In 0.75 Al 0.25 As quantum wells (QW) hosting a two-dimensional electron gas (2DEG) through molecular beam epitaxy (MBE). Internal charge-amplification mechanism can be achieved for very low applied voltages, while the high carrier mobility allows the design of very fast photon detectors with sub-nanosecond response times. This technology has been preliminarily exploited to fabricate prototype beam profilers with a strip geometry (with 50-μm-wide strips). Tests were carried out both with conventional X-ray tubes and at the Elettra synchrotron facility. The results testify how these profilers are capable of reconstructing the shape of the beam, as well as estimating the position of the beam centroid with a precision of about 400 nm. Further measurements with different samples of decreasing thickness have shown how this precision could be further improved by an optimised microfabrication. For this reason a new design, based on a membrane-photodetector, is proposed. Results regarding the spatial resolution as function of the sensor thickness will be presented and discussed.